Electrodeposition of a dendrite‐free 3D Al anode for improving cycling of an aluminum–graphite battery. Issue 2 (1st November 2021) - Li, Junfeng; Hui, Kwan San; Ji, Shunping; Zha, Chenyang; Yuan, Chengzong; Wu, Shuxing; Bin, Feng; Fan, Xi; Chen, Fuming; Shao, Zongping; Hui, Kwun Nam
Abstract: Aluminum–metal batteries show great potential as next‐generation energy storage due to their abundant resources and intrinsic safety. However, the crucial limitations of metallic Al anodes, such as dendrite and corrosion problems in conventional aluminum–metal batteries, remain challenging and elusive. Here, we report a novel electrodeposition strategy to prepare an optimized 3D Al anode on carbon cloth with an uniform deposition morphology, low local current density, and mitigatory volume change. The symmetrical cells with the 3D Al anode show superior stable cycling (>450 h) and low‐voltage hysteresis ( 170 mV) at 0.5 mA cm −2 . High reversibility ( 99.7%) is achieved for the Al plating/stripping. The graphite | | Al‐4/CC full batteries show a long lifespan of 800 cycles with 54 mAh g −1 capacity at a high current density of 1000 mA g −1, benefiting from the high capacitive‐controlled distribution. This study proposes a novel strategy to design 3D Al anodes for metallic‐Al‐based batteries by eliminating the problems of planar Al anodes and realizing the potential applications of aluminum–graphite batteries. Abstract : An optimized 3D Al anode with compact and uniform Al deposition on carbon cloth has tackled the challenge of the metallic–planar Al anode through the high surface area and conductivity of the 3D structure and is successfully applied to rechargeable aluminum–graphite batteries, showing better electrochemical behaviors.